Potentiometric NO2 Sensors Based on Thin Stabilized Zirconia Electrolytes and Asymmetric (La0.8Sr0.2)0.95MnO3 Electrodes - Jie Zou; Yangong Zheng; Junliang Li; Zhongliang Zhan; Jiawen Jian (Sensors, 2015)
Here we report on a new architecture for potentiometric NO2 sensors that features thin 8YSZ electrolytes sandwiched between two porous (La0.8Sr0.2)0.95MnO3 (LSM95) layers—one thick and the other thin—fabricated by the tape casting and co-firing techniques. Measurements of their sensing characteristics show that reducing the porosity of the supporting LSM95 reference electrodes can increase the response voltages. In the meanwhile, thin LSM95 layers perform better than Pt as the sensing electrode since the former can provide higher response voltages and better linear relationship between the sensitivities and the NO2 concentrations over 40–1000 ppm. The best linear coefficient can be as high as 0.99 with a sensitivity value of 52 mV/decade as obtained at 500 °C. Analysis of the sensing mechanism suggests that the gas phase reactions within the porous LSM95 layers are critically important in determining the response voltages.